Membangun Kompetensi Penulisan Teks Akademik “Panduan Praktis Untuk Mahasiswa” - Ertika Pasaribu; Iwain Nababan; Eka Putriani; Rahmi Siregar; Ika Febriana (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
In today's digital era, the ability to write effective and professional academic texts has become a very important skill for students. Writing academic texts is not just about writing, but also about how to convey ideas and arguments in a clear, logical and credible way. This article will discuss several important aspects of writing academic texts, including topic selection, research, organizing ideas, and effective writing. In an era of vast and rapidly developing information, the ability to write high-quality academic texts is the key to success in study and career. Students will not only use these skills in their studies, but also in their future jobs. Therefore, it is important for students to understand and develop their writing skills from an early age. In today's digital era, the ability to write effective and professional academic texts has become a very important skill for students. Writing academic texts is not just about writing, but also about how to convey ideas and arguments in a clear, logical and credible way. This article aims to help students understand and develop their writing skills, especially in an academic context. This article will discuss several important aspects of writing academic texts, including topic selection, research, organizing ideas, and effective writing.